Boosting ORR/OER Activity of Graphdiyne by Simple Heteroatom Doping. Issue 9 (16th May 2019) - Gu, Jinxing; Magagula, Saneliswa; Zhao, Jingxiang; Chen, Zhongfang
Abstract: Nitrogen‐doped graphdiynes recently emerged as promising metal‐free oxygen reduction reaction (ORR) electrocatalysts. However, which type of N‐dopants contributing to the enhanced catalytic performance and the catalytic performances of other heteroatom‐doped graphdiynes has not been explored systematically. Herein, ORR and oxygen evolution reaction (OER) catalytic performances of X‐doped graphdiynes are examined by means of DFT computations (X = B, N, P, and S). It is revealed that the graphitic S‐doped graphdiyne (Model S1), the sp‐N‐doped graphdiyne (Model N3) and the graphitic P‐doped graphdiyne (Model P1) exhibit comparable or even better ORR/OER activities than Pt/C or RuO2, with ORR activity trend as Model S1 > Pt/C > Model N3 and OER trend as Model P1 > RuO2 > Model N3. The carbon atoms near N‐ and S‐dopants and featuring large positive charge are the ORR active sites in Models N3 and S1, whereas the carbon atoms near N‐ and P‐dopants and possessing high spin are the OER active sites in Models N3 and P1. Overall, this study not only gains deep insights into the catalytic activity of N‐doped graphdiyne for ORR, but also guides developing of graphdiyne‐based ORR/OER catalysts beyond N‐doping. Abstract : By means of density functional theory computations, the catalytic performances of B‐, N‐, P‐ and S‐doped graphdiyne for the oxygen reduction and evolution reactions (ORR and OER) are systematically investigated. It is demonstrated that the sp‐N dopant is crucial for high activities of N‐doped graphdiyne. S‐doped and P‐doped graphdiyne outperform commercial Pt/C for ORR, and RuO2 for OER catalysis respectively.